The parathyroid glands identification of carbon nanoparticles via preoperative injection in reoperation of recurrent benign multinodular goiter - Wang, Yonghui; Li, Quancai; Fan, Mingxiu; Ming, Kunxiu (Frontiers in Endocrinology, 2024)
Introduction Benign multinodular goiter (BMNG) can grow very large and cause compression symptoms, making the operation procedure difficult. However, the recurrence rate of BMNG ranges from 3% to 43%. Reoperative thyroid surgery for BMNG is uncommon and can result in a high rate of complications, including hypoparathyroidism and recurrent laryngeal nerve palsy. Carbon nanoparticles (CNs) have been widely used as a protective agent for the parathyroid gland and as a tracer agent in central lymph node dissection. However, the protection effect of CNs in redoing BMNG has not been well illustrated. This study investigates whether CNs could protect parathyroid glands (PGs) during reoperation for patients with BMNG. Methods BMNG patients who previously underwent thyroidectomy and received reoperation between January 2019 and January 2022 were retrospectively recruited. The Dunhill approach was employed for all patients. The patients were divided into two groups: the CNs group, who received injection CNs injection 1 hour before the operation (n = 24), and the control group, who underwent thyroid surgery without CNs injection (control group, n = 25). The numbers of PGs preserved in situ, autotransplantation, the accidental removal of the PGs, and the parathyroid hormone level were recorded and analyzed. Results The results revealed that more PGs were preserved in situ in the CNs group compared to the control group (3.25±0.15 vs 2.60±0.16, P=.007). Moreover, fewer PGs were subjected to autotransplantation and were accidentally discovered in the specimen in the CNs group compared to the control group. Patients who had CNs injection exhibited a lower rate of transient (5/24 vs. 13/25, P=.024) and permanent hypoparathyroidism (2/24 vs. 9/25, P=.020) compared to the control group.